The Interaction Effect of Preference and Availability on Brand Switching and Market Share - Jeuland, Abel P. (Management Science, 1979)
Observed purchase behavior is the result of the combined effect of preference and availability. A multibrand choice model of a frequently purchased consumer good is developed. The model allows for the heterogeneity of the population with respect to brand preference. It also considers that all brands are not identically distributed and are thus not equally available to the potential buyers of the product class. The model uses the brand switching matrix in order to parcel out the effect of preference and availability. It is compared with the Hendry System which also uses the brand switching matrix for the purpose of measuring brand substitution or competition. The Hendry System being a special case of the model presented in this paper, the likelihood ratio test is employed to test the more general model against Hendry. The estimation and testing procedure uses cooking oil data from 1,961 households who remained in the Secodip Consumer Panel, France, for the entire 1971–1972 period. The variable of availability is found to account for an additional significant portion of the variance of the switching flows. The model should prove to be a useful tool to interpret correctly the popular quantitative summary of multibrand markets, namely the switching matrix. More efficient use of panel data by marketing decision makers should result.